Landscape, nature, and the sacred in Byzantium - Della Dora, Veronica (Cambridge University Press, 2016)
"Nature is as much an idea as a physical reality. By 'placing' nature within Byzantine culture and within the discourse of Orthodox Christian thought and practice, Landscape, Nature and the Sacred in Byzantium explores attitudes towards creation that are utterly and fascinatingly different from the modern. Drawing on Patristic writing and on Byzantine literature and art, the book develops a fresh conceptual framework for approaching Byzantine perceptions of space and the environment. It takes readers on an imaginary flight over the Earth and its varied topographies of gardens and wilderness, mountains and caves, rivers and seas, and invites them to shift from the linear time of history to the cyclical time and spaces of the sacred - the time and spaces of eternal returns and revelations"--